Incarcerating juveniles in adult prisons: examining the relationship between age and prison behavior in transferred juveniles - Kolivoski, Karen M. (Criminal justice and behavior, 2016)
The experiences of juveniles in adult prisons have gained increased attention over the last several decades. This article adds to understandings of these experiences by examining the relationship between age and prison behavior among transferred juveniles (N = 763). Results reveal that juveniles committed to prisons at younger ages accumulate more misconducts than those committed at older ages. Results also indicate that African American youth, youth with mental health issues, youth with more extensive prior histories in the juvenile system, and youth committed for property and weapons offenses accumulated more prison misconducts. Policy and practice implications are discussed.